2014
DOI: 10.1128/ec.00336-13
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Triggers NLRP3-Mediated Pyroptosis in Macrophages

Abstract: Pyroptosis is an inflammasome-mediated programmed cell death pathway triggered in macrophages by a variety of stimuli, including intracellular bacterial pathogens. Activation of pyroptosis leads to the secretion of interleukin-1␤ (IL-1␤) and pore-mediated cell lysis. Although not considered an intracellular pathogen, Candida albicans is able to kill and, thereby, escape from macrophages. Here, we show that C. albicans-infected bone marrow-derived macrophages (BMDM) and murine J774 macrophages undergo pyroptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
226
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(246 citation statements)
references
References 48 publications
18
226
0
2
Order By: Relevance
“…It is well recognized that NLRP3 inflammasome activation induced caspase 1-dependent cell death, named pyroptosis. 16,17 Caspase 1 activation assay and IL-1β ELISA assay showed that significant caspase 1 activation (Figure 4h and i) and IL-1β secretion (Figure 4j and k) were detected in the NLRP3 inflammasome reconstituted cells. These data indicate that NLRP3 inflammasome reconstitution induced caspase 1-dependent pyroptosis.…”
Section: Reconstitution Of Nlrp3 Inflammasome Reversed Malignant Behamentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that NLRP3 inflammasome activation induced caspase 1-dependent cell death, named pyroptosis. 16,17 Caspase 1 activation assay and IL-1β ELISA assay showed that significant caspase 1 activation (Figure 4h and i) and IL-1β secretion (Figure 4j and k) were detected in the NLRP3 inflammasome reconstituted cells. These data indicate that NLRP3 inflammasome reconstitution induced caspase 1-dependent pyroptosis.…”
Section: Reconstitution Of Nlrp3 Inflammasome Reversed Malignant Behamentioning
confidence: 99%
“…16,17 Recent study showed that pyroptotic cell death of hepatocyte mediated liver damage. 30 Another study showed that NLRP3 inflammasome activation contributed to the progression of non-alcoholic fatty liver disease.…”
mentioning
confidence: 99%
“…Although it is tempting (and dramatic) to speculate that these hyphae kill by exerting pressure on the macrophage membrane and physically breaking through, recent reports from our lab and others suggest that other mechanisms, related to regulation of the host-pathogen 'synapse', mediate host cell death and pathogen escape from macrophages 9,10 .…”
Section: Developmental Transitions Allow C Albicans To Adapt and Surmentioning
confidence: 99%
“…The key result that showed that C. albicans does not simply break macrophages, but rather induces a more regulated mechanism of killing, came with the realisation that macrophages derived from mice deficient in a central host immune pathway -the caspase 1 inflammasome -were protected from killing by C. albicans in the first few hours post-phagocytosis 9,10 . This was despite normal formation of fungal hyphae, and therefore it argued that physical disruption of macrophages by fungal filaments is not the only mechanism of host cell death.…”
Section: Developmental Transitions Allow C Albicans To Adapt and Surmentioning
confidence: 99%
See 1 more Smart Citation